Three-dimensional nanotube electrode arrays for hierarchical tubular structured high-performance pseudocapacitors. Issue 27 (23rd June 2016) - Gao, Yuan; Lin, Yuanjing; Chen, Jiaqi; Lin, Qingfeng; Wu, Yue; Su, Wenjun; Wang, Wenli; Fan, Zhiyong
Abstract : The unique hierarchical tubular pseudocapacitor electrode prepared via a cost-effective ultrasonic spray pyrolysis (USP) method shows remarkable performance enhancement in both volumetric and areal capacitance. Abstract : Ordered three-dimensional (3-D) tubular arrays are highly attractive candidates for high performance pseudocapacitor electrodes. Here, we report 3-D fluorine doped tin oxide (FTO) tubular arrays fabricated by a cost-effective ultrasonic spray pyrolysis (USP) method in anodic aluminum oxide (AAO) channels with high uniformity. The large surface area of such a structure leads to remarkable surface area enhancement up to 51.8 times compared to a planar structure. Combining with electrochemically deposited manganese dioxide (MnO2 ) nanoflakes on the inner side wall of the FTO nanotubes, the unique hierarchical tubular structured pseudocapacitor electrode demonstrated the highest areal capacitance of 193.8 mF cm −2 at the scan rate of 5 mV s −1 and 184 mF cm −2 at the discharge current density of 0.6 mA cm −2, which is 18.5 times that of a planar electrode. And it also showed a volumetric capacitance of 112.6 F cm −3 at the scan rate of 5 mV s −1 and 108.8 F cm −3 at the discharge current density of 0.6 mA cm −2 . In addition, the cyclic stability test also indicated that a nanostructured pseudocapacitive electrode has a much larger capacitance retention after 3000 cycles of the charge–discharge process compared with a planar electrode, primarily due to the mechanical stability of the nanostructure. Moreover, pseudocapacitor device fabrication based on such electrodes shows the volumetric capacitance of 17.5 F cm −3, and the highest specific energy of 1.56 × 10 −3 Wh cm −3 . With the merit of facile fabrication procedures and largely enhanced electrochemical performance, such a 3-D structure has high potency for energy storage systems for a wide range of practical applications.